PTEN Sequence Analysis in Endometrial Hyperplasia and Endometrial Carcinoma in Slovak Women - H. Gbelcová; P. Bakeš; P. Priščáková; V. Šišovský; I. Hojsíková; Ľ. Straka; M. Konečný; J. Markus; C. W. D’Acunto; T. Ruml; D. Böhmer; Ľ. Danihel; et al. (Analytical Cellular Pathology)
Phosphatase and tensin homolog (PTEN) is a protein that acts as a tumor suppressor by dephosphorylating the lipid second messenger phosphatidylinositol 3,4,5-trisphosphate. Loss of PTEN function has been implicated in the pathogenesis of a number of different tumors, particularly endometrial carcinoma (ECa). ECa is the most common neoplasia of the female genital tract. Our study evaluates an association between the morphological appearance of endometrial hyperplasia and endometrial carcinoma and the degree of PTEN alterations. A total of 45 endometrial biopsies from Slovak women were included in present study. Formalin-fixed and paraffin-embedded tissue samples with simple hyperplasia (3), complex hyperplasia (5), atypical complex hyperplasia (7), endometrioid carcinomas G1 (20) and G3 (5), and serous carcinoma (5) were evaluated for the presence of mutations in coding regions of PTEN gene, the most frequently mutated tumor suppressor gene in endometrial carcinoma. 75% of the detected mutations were clustered in exons 5 and 8. Out of the 39 mutations detected in 24 cases, 20 were frameshifts and 19 were nonsense, missense, or silent mutations. Some specimens harboured more than one mutation. The results of current study on Slovak women were compared to a previous study performed on Polish population. The two sets of results were similar.